Tratamentos pré-germinativos visando minimizar a dormência em sementes de tucumã (astrocaryum aculeatum g. Mey.) - Nazário, Patrícia (Instituto Nacional de Pesquisas da Amazônia - INPA, 2006)
This study evaluated the effect of water content and germination pretreatments on Astrocaryum aculeatum and identified possible causes of dormancy. A supplementary study was made in the anatomy and histochemistry of the seed integument. The emergence of plants was favored by soaking independent of temperature and period, but the lower mean time was in a 40ºC soak for six days. Seeds with 28% of water submitted by heat pretreatment (35°C or 40°C) showed higher emergence of seedling and emergence speed index and lower emergence times than those whose the water content was 21%. In closed plastic bags, the heat pretreatment (40°C), independent of the initial seed water content or the treatment period was favorable to Astrocaryum aculeatum germination. The emergence variables, fats and phenol contents and lipid melting points varied among the A. aculeatum progenies. The emergence and the emergence speed index were negatively correlated with the fat contents and positively correlated with the lipid melting point and this was negatively correlated with dead seeds. A. aculeatum seeds inhibited germination of lettuce seeds. The seed integument is impregnated with phenols and there are differences in integument cell disposition and size between the opercule integument and other regions.
Keywords: palm; soaking; Temperatura; inhibitors; Germination; Palmeiras; embebição; Temperatura; inibidores; Germinação